2020
DOI: 10.1186/s12909-020-02433-6
|View full text |Cite
|
Sign up to set email alerts
|

Vertical integration in medical education: the broader perspective

Abstract: Curricular integration represents collaborations between disciplines to establish a coherent curriculum and has become the dominant recommendation for medical education in the second half of the twentieth century. Vertical integration specifically is the integration between the clinical and basic science parts throughout the program. Vertically integrated curricula present basic sciences imbedded in a clinical context from the start of medical school.The authors briefly discuss vertical integration in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 31 publications
2
53
0
6
Order By: Relevance
“…[ 12 20 25 ] The integration of basic and clinical sciences showed that the students understood the connection between basic and clinical sciences better when the content was co-taught. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 20 25 ] The integration of basic and clinical sciences showed that the students understood the connection between basic and clinical sciences better when the content was co-taught. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the University of Wisconsin School of Medicine and Public Health (UWSMPH) embarked on a curriculum redesign following recommendations from the 2010 Carnegie Foundation report, which encouraged medical schools to move toward a more integrated curriculum and away from traditional medical education [ 1 , 2 ]. Vertical integration, specifically, aligns well with the goals of several learning theories, including adult learning and motivation theories to enhance learning [ 3 ]. The new curriculum, named the ForWard curriculum, features an integrated design of the required preclinical and core clinical coursework and replaced a traditional 2 + 2 curriculum, referred to as the Legacy curriculum [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1] The curriculum is simply a stack of separate courses which are discipline based and teacher centered. [2] Our medical school followed a traditional curriculum earlier, and due to a large amount of content embedded in each discipline, which facilitated less scope for active and deep learning. In addition, the use of lectures as a predominant teaching-learning method and lack of active learning strategies do not provide enough opportunity for the students to engage in self-directed learning.…”
Section: Introductionmentioning
confidence: 99%